An analysis of crime reporting (and audience perceptions of it) in selected South African media - Daan du Plessis (Communicare)
The study on which this article was based was part of an international news study, conducted in 10 countries (Australia, China, Chile, Germany, India, Israel, Jordan, Russia, South Africa and the USA). In this article, the way in which crime as a topic is dealt with in selected news media is explored. Focus group results were also analysed to establish how people perceive crime reporting. Shoemaker’s theory on news values is applied to analyse media content and results from focus groups. From the analysis, it emerged that the media perform a surveillance function on behalf of their audiences and that the news media apply regular news values to decide on the reporting and presentation of news items dealing with crime events. Media audiences make practical use of information provided by the media on crime events to take precautions or to become aware of dangerous situations and people. Shoemaker’s theory also provides a valuable framework according to which news content can be analysed and understood. The data used in this study was collected as part of the What’s News? Project, based at the S.I. Newhouse School of Public Communications, Syracuse University, Syracuse, New York, USA, and is part of a larger study of the definition of news in ten countries. The principal investigators are Dr Pamela J. Shoemaker (Syracuse University) and Dr Akiba Cohen (Tel Aviv University, Israel). Additional researchers participated in the study from the following countries: Australia, China, Chile, India, Israel, Germany, Jordan, Russia, South Africa and the United States. Syracuse University acknowledges the support of the John Ben Snow Foundation.